Review of Material Supply Chain Management during Pre-construction Phases in Malaysia - Loh Yong Seng; Salman Riazi Mehdi Riazi; Mohd Nasrun Mohd Nawi; Radzi Ismail (International Journal of Supply Chain Management, 2018)
Construction materials play significant role in construction industry which therefore requires fully attention when creating project plan. Materials form a large part in total cost of construction project. The absence of materials when needed is one of the main causes of loss of productivity in a worksite. Current materials management practices in the construction industry are performed on fragmented basis with many problems faced when managing material supply chain, especially during pre-construction phases. These problems are the main root that causing performance-related problems such as delay in material ordering and receiving, low productivity, cost and time overrun, conflict and disputes. Thus, this paper reviews and discusses the activities and problems faced in material supply chain management during pre-construction phases. It also reasons out on the potential of SCM to be the way forward for improving problems of construction industry (i.e. material supply chain management). A series of in-depth literature review was conducted towards digging the relevant points towards achieving the aims of this paper. In the end, it was clear that material supply chain practices at pre-construction phases are still at below optimum level and that SCM literatures strongly support of it being the potential saviour.